Evolutionary Analysis of Mammalian ACE2 and the Key Residues Involved in Binding to the Spike Protein Revealed Potential SARS-CoV-2 Hosts - Luciano Rodrigo Lopes1; Natália Carvalho de Lucca Pina1; Antonio Carlos da Silva Junior1; Paulo- Bandiera Paiva1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2) spilled over to humans via wild mammals, entering the host cell using angiotensin-converting enzyme 2 (ACE2) as receptor through Spike (S) protein binding. While SARS-CoV-2 became fully adapted to humans and globally spread, some mammal species were infected back. The present study evaluated the potential risk of mammals becoming hosts for SARS-CoV-2 through bioinformatics prediction based on ACE2 receptors. Methods: We used evolutionary bioinformatic approaches and comparative analysis of ACE2 critical residues that bind SARS-CoV-2 S-protein and predicted potential SARS-CoV-2 hosts among mammals and assessed their risk. Results: ACE2 phylogenetic tree placed primates close to rodents and rabbits. Felines, rodents, and rabbits had higher ACE2 similarities than human ACE2 (hACE2). Farmed animals, such as bovids, swine, and equids, had similar ACE2 compared to hACE2; however, these animals showed low SARS-CoV-2 susceptibility. Some cetaceans also presented high similarities in ACE2 key residues with hACE2. Conclusion: Here, we showed wild and domestic mammals with a low divergence of ACE2 compared to humans, discussing their possible chance of being infected, especially those animals kept as livestock or pets. Regarding the feasible transmission through contaminated water, cetaceans can be at risk of SARS-CoV-2 infection. Extensive surveillance of SARS-CoV-2 should be applied to prevent new coronavirus outbreaks and preserve mammals from infectious threats.